Silicon dioxide recycling from palm oil mill fuel ash waste (POMPAW) by using acid leaching ultrasound wave (ALUW) - Norazuwen, Rusli (2017)
Palm oil mill fuel ash waste (POMFAW) is highly potential renewable source of silicon dioxide. Silicon dioxide is also well-known as silica has been applied widely in many industries these days. Therefore, it is important to use this approach to utilize the POMFAW since Malaysia nowadays continuously producing biomass wastes. This paper demonstrates experimentally the method on silicon dioxide recycling from palm oil mill fuel ash waste (POMFAW) by using acid leaching ultrasound wave (ALUW). In this study, there are 3 parameters has been investigated which are the treatment time, acid concentration and irradiation power in order to identify the optimum condition to extract silica from POMFAW by using ultrasonic-assisted acid leaching method. Thus, the maximum amount of silica that can be extracted from POMFAW is up to 84.12% by using the sulphuric acid at 2M concentration at 450W of sonication power at the treatment time of 30 minutes.